PSYCHOSOCIAL SAFETY CLIMATE AND WORK-SCHOOL CONFLICT IN WORKING UNIVERSITY STUDENTS - Renny Azaria; Artiawati Artiawati; Krismasita Surya Putri; Cindy Angelica Lawrence (Universitas Ahmad Dahlan, 2023)
Students who are also working experience various difficulties in managing their working life and their studies at the same time. This can lead to work-school conflict. Psychosocial safety climate in the work environment can be an antecedent because it can reduce work-school conflict. This study aims to examine the relationship between psychosocial safety climate and work-school conflict in working students. Data were collected using the PSC-12 and WSC scales through a Google Form. A total of 108 working students, selected through a convenience sampling method, participated in this study. Data analysis was done using multiple regression analysis tests. The results showed that psychosocial safety climate was able to predict work-school conflict (R2 = 0.067; p = .007, p < 0.05). Aspects of management support and commitment have the most significant role among the aspects of psychosocial safety climate in predicting work-school conflict in working students.